Frequency of Bacterial Vaginosis and its Fetomaternal Consequences: A prospective study - Shaza Khan, Muhammad Asim Iqbal, Ayesha Munir, Pari Imam Gul, Asma Mumtaz, Mian Adnan Aslam, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the incidence rate of bacterial vaginosis in pregnant women and to ascertain its obstetric consequences. Study design: A prospective, cohort study Place & duration of study: From 3rd June 2020 to 3rd June 2021 in the gynecology department of Nishtar Medical Hospital. Methodology: A total of 250 pregnant women who have surpassed their 10 weeks of gestation were included in the study. Vaginal swab samples were collected and microbiological testing was performed. Nugent scores and Amsel's composite criteria were used for diagnosing bacterial vaginosis and classifying women into bacterial vaginosis, non-bacterial vaginosis, and intermediate bacterial vaginosis. A mid-sample urine sample was also cultured to diagnose urinary tract infection in analyzed women. All women were then followed-up during the remaining pregnancy course for adverse antenatal events and newborn conditions were also observed. Results: Out of the total of 250 women, 19.2% were diagnosed positive for bacterial vaginosis. Candidiasis was the second-largest reported infection among the analyzed women affecting 4.8% of women. Bacterial vaginosis was significantly higher in women aged between 18-25 years, in nulliparous women, and those in lower social class (p<0.05). Abortion (6.25%), preterm labor (43.7%), premature rupture of membranes (PROM) (27%), and puerperal pyrexia (4.1%) were the most considerable adverse outcomes and were significantly higher in the bacterial vaginosis group. Conclusion: Bacterial vaginosis is significantly higher in pregnant women and is associated with adverse pregnancy outcomes such as abortion, preterm labor, puerperal pyrexia, and premature rupture of membrane